Peculiarities of practical application of offset of counter homogeneous requirements in the liquidation procedure - Чубар, Тетяна (Theory and practice of jurisprudence, 2017)
The article is devoted to the peculiarities of practical application of uniform admission counter claims in the liquidation proceedings. The author of the essence, main content and implications of the liquidation proceedings in respect of an insolvent debtor. Analyzed the sequence of creditors’ claims based on the principle of proportionality satisfaction of one stage and the full satisfaction of the previous turn. The analysis of the category «redeemed requirements» and explored grounds for termination of obligations, including the way other than performance, including admission counter homogeneous requirements. Singled out a number of requirements that might be counter admission of similar claims in the liquidation proceedings, and formulated and analyzed the claims of creditors repayment terms by transferring counter homogeneous claims in the liquidation proceedings, such as: the provision of appropriate consent of the creditor (creditors); and if it does not violate the property rights of other creditors. In addition, the author provided the answer to the question whether admission requirements to be counter-homogeneous form of payment in the sale of property of the debtor (bankrupt). Summarizing the author concludes, and that although the law stipulates repayment of creditors’ claims by transferring counter homogeneous claims in the liquidation proceedings subject to a corresponding agreement of the creditor (creditors) and if it does not violate the property rights of other creditors, in practice this institute can undoubtedly be applied in the liquidation procedure only if the full satisfaction of all claims of bankruptcy creditors according to priority creditors’ claims, and in the case of «implementation» illiquid residual masses «opposite» lender.